Philosophy of socialism - Ahmad, Z . A. (Allahabad, 1940)
Philosophy is commonly considered to be a domain in which a few learned individuals indulge in the luxury of constructing and destroying imaginary worlds. The so-called practical people often sneer at philosophical discussion. Life is too short, they say, to allow us to enquire into the why and wherefore of things; it is best to take facts as they are. And yet everyone is in a way a philosopher. It is indeed impossible to find an individual who has no beliefs, convictions, prejudices or notions of good or bad. In fact, an average man has a fairly well defined set of values; his thought is governed by certain assumptions on the basis of which he explains everything, even the most complicated natural and social phenomena. It is these values, beliefs and assumptions which constitute a man's philosophical outlook. For, after all the real object of philosophy is to explain nature and society, to distinguish the real from the unreal and the cause from the effect. Thus, the individual has no choice whether he shall have philosophical beliefs or not, only the choice whether his philosophical beliefs shall be conscious or unconscious.
Keywords: Socialism